2007
DOI: 10.1203/pdr.0b013e3180332d36
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Brief Exercise on Circulating CD34+ Stem Cells in Early and Late Pubertal Boys

Abstract: ABSTRACT:We tested the hypothesis that exercise could stimulate CD34ϩ peripheral blood hematopoietic stem cells (PBSC) in children. Fourteen early pubertal boys (EP, age 10.3 Ϯ 0.3 y) and 13 late pubertal boys (LP, age 16.5 Ϯ 0.4 y) performed 20 min of moderateto-vigorous cycle ergometer exercise. Blood was drawn before and after exercise. Cells were stained for surface CD34ϩ . Plasma granulocyte colony stimulating factor (G-CSF), Fms-like tyrosine kinase-3 (FLT-3), and stromal cell-derived factor-1 (SDF-1) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 30 publications
2
31
2
1
Order By: Relevance
“…Our programme, which consisted of a combination of aerobic and resistance training, resulted in an increase in the percentage of CD34 + and CD133 + cells in children who exercised. Similar findings have been recently reported by Zaldivar and colleagues [20], who showed that a brief bout of moderate to vigorous cycling exercise resulted in a significant increase in CD34 + (haematopoietic stem cells) in pubertal boys. However, to our knowledge these data provide the first evidence that combined aerobic and resistance exercise training may represent an effective strategy to improve vascular repair markers in overweight and obese children.…”
Section: Discussionsupporting
confidence: 91%
“…Our programme, which consisted of a combination of aerobic and resistance training, resulted in an increase in the percentage of CD34 + and CD133 + cells in children who exercised. Similar findings have been recently reported by Zaldivar and colleagues [20], who showed that a brief bout of moderate to vigorous cycling exercise resulted in a significant increase in CD34 + (haematopoietic stem cells) in pubertal boys. However, to our knowledge these data provide the first evidence that combined aerobic and resistance exercise training may represent an effective strategy to improve vascular repair markers in overweight and obese children.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, seventeen cross-sectional studies evaluated by Woods et al (2006) reported an inverse correlation between physical activity and CRP levels. Moreover, brief exercise in young adolescent males has been shown to significantly increase a chemokine protein called chemokine (CXC Motif) ligand 12 (CXCL12) [formerly known as stromal cell-derived factor 1], an important factor involved in angiogenesis (Zaldivar et al, 2007). …”
Section: Putative Mechanisms Underlying the Relationship Of Physical mentioning
confidence: 99%
“…It has been known for decades that individual bouts of exercise lead to an increase in circulating leukocytes and even stem cells (1,10,24,91,114,158). This is a remarkably reproducible, substantial, somewhat dose-dependent phenomenon known to exist in children and adults, as well as in other mammals (34,55,64,105).…”
Section: The Stress and Inflammatory Response To Exercisementioning
confidence: 99%